Reactive oxygen species (ROS)-responsive tellurium-containing hyperbranched polymer. Issue 15 (17th February 2015) - Fang, Ruochen; Xu, Huaping; Cao, Wei; Yang, Liulin; Zhang, Xi
Abstract : Tellurium-containing hyperbranched polymers form aggregates, which are a new kind of material responsive to reactive oxygen species at a physiological level. Abstract : Materials responsive to reactive oxygen species (ROS) at a physiological level are of great significance in diagnostic and therapeutic applications. We have synthesized a water-soluble tellurium-containing hyperbranched polymer and demonstrated that it forms a kind of ROS-responsive aggregate. In aqueous environment, the polymer aggregates can swell under biologically relevant concentration of H2 O2, which could be expected to find applications in fields such as elimination of excess ROS.